2022
DOI: 10.1186/s12913-022-07483-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medicare comprehensive medication review on racial/ethnic disparities in nonadherence to statin medications among patients with Alzheimer’s Disease: an observational analysis

Abstract: Background Alzheimer’s Disease (AD) is the mostcommon cause of dementia, a neurological disorder characterized by memory loss and judgment impairment. Hyperlipidemia, a commonly co-occurring condition, should be treated to prevent associated complications. Medication adherence may be difficult for individuals with AD due to the complexity of AD management. Comprehensive Medication Reviews (CMRs), a required component of Medicare Part D Medication Therapy Management (MTM), have been shown to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Previous research has found that MTM programs can improve medication adherence rates, highlighting the value of such intervention in medication management led by pharmacists or other qualified providers. 25 , 26 Results from this study also reconfirmed the benefits of CMRs (a required component of the MTM services) on the population of interest. As stated above, one possible reason for this population's low medication adherence rate is the complexity of COPD medication regimens.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous research has found that MTM programs can improve medication adherence rates, highlighting the value of such intervention in medication management led by pharmacists or other qualified providers. 25 , 26 Results from this study also reconfirmed the benefits of CMRs (a required component of the MTM services) on the population of interest. As stated above, one possible reason for this population's low medication adherence rate is the complexity of COPD medication regimens.…”
Section: Discussionsupporting
confidence: 59%
“…24 It has been found previously in the U.S. and other countries that MTM programs, including CMRs, are associated with higher medication adherence rates, reduced healthcare costs, and decreased racial/ethnic disparities in medication nonadherence rates. 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“… 24 Even among complex Alzheimer's patients, receiving a CMR reduces ethnic disparities in medication adherence to statin medications between Hispanic and White patients. 25 The current study's findings reveal that racial/ethnic minorities are not receiving all MTM services as equally as White patients, suggesting disparities in receiving the associated benefits. This could worsen the already existing and well-documented racial/ethnic disparities in health care.…”
Section: Discussionmentioning
confidence: 57%
“…Two studies reported on potentially inappropriate medication use—“drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies.” 58 One study reported higher rates of potentially inappropriate medication use in Hispanic Americans compared to NHW persons 58 and another found higher rates of concurrent use of medications with anti‐cholinergic properties and anti‐dementia medications in NHW and Native Hawaiians compared to Asian Americans 59 . Finally, several studies reported racial/ethnic differences in patterns of use of drugs for hypertension and other medical conditions in PLWD 46,60,61 . Among the studies of medication for other medical conditions, a Medicare Comprehensive Medication Review was found to reduce disparities in statin non‐adherence for Hispanic American PLWD 61 .…”
Section: Resultsmentioning
confidence: 98%
“… 59 Finally, several studies reported racial/ethnic differences in patterns of use of drugs for hypertension and other medical conditions in PLWD. 46 , 60 , 61 Among the studies of medication for other medical conditions, a Medicare Comprehensive Medication Review was found to reduce disparities in statin non‐adherence for Hispanic American PLWD. 61 In a related study, Hispanic and Asian Americans were more likely to be similarly enrolled in Medication Therapy Management (MTM) programs compared to NHW, and Black Americans were less likely to be enrolled in MTM than NHW.…”
Section: Resultsmentioning
confidence: 99%